1941
DOI: 10.1111/j.1939-0025.1941.tb05781.x
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine (benzedrine) therapy of children's behavior disorders.

Abstract: Northern Masonic Jurisdiction, U. S. A. Amphetamine sulfate (benzedrine sulfate S.K.F.) and placebos supplied by Smith, KIine and French Laboratories, Philadelphia. 9 2 ___ Age in Years Daily Dose I -7 r-, -____-, --.-8 9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
7

Year Published

1942
1942
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(41 citation statements)
references
References 7 publications
2
32
0
7
Order By: Relevance
“…They act in fact as psycholeptics in these cases. This effect was described in 1937 by Bradley and Bowen (9) and has since been corroborated in numerous uncontrolled and a few controlled experi ments (surveys: 12, 18, 56). Only one double-blind study yielded negative results (51), but it entailed a low amphetamine dosage and its duration (2 weeks) may have been too short to produce any effect.…”
Section: D) Stimulantsmentioning
confidence: 91%
“…They act in fact as psycholeptics in these cases. This effect was described in 1937 by Bradley and Bowen (9) and has since been corroborated in numerous uncontrolled and a few controlled experi ments (surveys: 12, 18, 56). Only one double-blind study yielded negative results (51), but it entailed a low amphetamine dosage and its duration (2 weeks) may have been too short to produce any effect.…”
Section: D) Stimulantsmentioning
confidence: 91%
“…[2]. Il a constaté une amélioration clinique dans 60 à 75% des cas, l'absence d'effet dans 15 à 25% et des effets secondaires indésirables dans 10 à 15% surtout dans les premiers jours.…”
Section: Introductionunclassified
“…L'efficacité de la dextroamphétamine (DEX, Dexamin ® ) est connue depuis de nombreuses années [2,[11][12][13], mais des études signalent l'incidence un peu plus élevée d'effets secondaires [14][15][16].…”
Section: Introductionunclassified
“…Yet hyperactive children are given stimulants to " calm " them down, despite the fact that science would predict stimulants would increase hyperactivity. Bradley (1937Bradley ( , 1950 observed that half of the behaviorproblem children to whom he administered a stimulant for one week became subdued. He called this fi nding paradoxical, speculating that inhibitory centers of the central nervous system were stimulated.…”
mentioning
confidence: 99%